PROPOSE MARKETING STRATEGY THROUGH PRODUCT DIFFERENTIATION AND SOCIAL MEDIA MARKETING APPROACH FOR FASHION READY TO WEAR (CASE STUDY: KYAK WEAR) (The Indonesian Journal of Business Administration, 2019)
Indonesia’s fashion and lifestyle are currently getting more exposed to local consumers since the products works in term of quality that are not inferior and have potential to compete in international market. In addition, this state is effected the consumers who want to show their own personal style distinctively, which makes the fashion products needs to be more specific to target consumers. From statistica.com’s data expected 19% of total market revenue in clothing sector will be generated through online sales in 2022Kyak Wear is a ‘ready to wear’ fashion brand which initially started with specialization in women's clothing. The products is intended to have comfort appearance combined with unique and bold style. Although now, fashion products it’s a big and potential market, Kyak Wear has not been able to achieve its desired sales. To evaluate the problem Kyak Wear using 7p marketing analysis to examine more about its product differentiation and its digital marketing because those two things has not been able fully optimized by Kyak Wear. The Methodology used in this research is mixed-methods research methodologies, with data collection done through surveys and questionnaires which distributed to the samples of customer. The data is then used to be analyzed and compared with the actual data from Kyak Wear. If there is a gap between the data, the gap will be reviewed to confirms the main causes of the problem and how to provide the solutions. Then, the result of the research are; 1. the key of product differentiation is in the signature of material, 2. Update all 7p marketing mix factors, 3.Optimize a social media markeitng specifically instagram and website with realiable service.Keywords : ready to wear fashion business, marketing strategy, product differentiation, social media, 7p marketing mix